Pendekatan Bermain Kreatif sebagai Metode Pembelajaran pada Anak Usia Dini - Monika Rahel; Itsnain Alfajri Husain (FKIP UNSULTRA, 2026)
The creative play approach is an essential learning method in early childhood education as it supports children’s holistic development. This study aims to analyze the implementation of the creative play approach in early childhood education through a literature review of scientific sources, books, and educational journals. The method used is library research involving the collection and analysis of relevant literature on creative play, child development, and early childhood education strategies. The results indicate that the creative play approach contributes to the development of children’s cognitive, social-emotional, language, motor, and creativity skills. More importantly, the findings suggest that creative play functions as an integrative learning approach that simultaneously stimulates multiple domains of child development rather than isolated skills. In addition, creative play enhances children’s self-confidence, problem-solving skills, and social interaction during learning activities. Teachers play a crucial role as facilitators in creating a joyful learning environment that supports children’s exploration. The use of varied learning media also supports the effectiveness of this approach. Furthermore, learning based on creative play makes children more active, enthusiastic, and able to understand learning materials more easily compared to conventional learning methods. Thus, the creative play approach can be considered an effective learning method in early childhood education as it aligns with children’s natural learning characteristics, which emphasize learning through play.